The Disparate Approaches of General Practitioners to the Pharmaceuticalisation of Cardiovascular Disease Prevention - Douglass, Tom; Calnan, Michael (Frontiers in Sociology, 2021)
In the context of current clinical practice guidance, this paper will analyse the role of GPs in decision-making about the primary prevention of cardiovascular disease (CVD) using the concept of pharmaceuticalisation. Drawing on thematic analysis of semi-structured interviews with 20 GPs, the paper argues that the way GPs approach CVD pharmaceuticalisation is shaped by their understandings of and use of guidelines (and the knowledge they embody), existing treatment perspectives and the moral qualities of preventative treatment, and professional evaluations of ‘relevant’ information. The analysis indicates that there exist disparate and distinct approaches to and understandings of CVD pharmaceuticalisation amongst GPs. Depending on how knowledge, treatment perspectives and values variously combine, GPs sit somewhere on a spectrum of how pharmaceuticalised they are in terms of the approaches to and understandings of the prevention of CVD.